Variability simulations of joist floor systems - Goodman, J. R., author; Criswell, M. E., author; Thompson, E. G., author; Dawson, P. R., author; Bodig, J., author; Colorado State University. Department of Civil Engineering, publisher (Colorado State University. Libraries, 1974)
This thesis examines the use of the Monte Carlo method for studying the effects of component variability on the deflection behavior of wood joist floor systems. The study considers random variations in joist modulus of elasticity within a lumber grade and evaluates this effect on floor deflection behavior. Simulation results indicate that there are two basic effects induced on deflection behavior by joist modulus of elasticity variability. These effects are changes in mean maximum floor deflection and maximum floor deflection variability. A means for seeking optimum economic efficiency through restricting component variability to a value that yields the best floor maximum deflection response to component cost relationship can be formulated from floor maximum deflection distributions. The study emphasizes that important roles of structural interaction and component variability on structural performance. For floors in which a deflection criterion governs design, the design calculation is normally based on the deflection behavior of joists with average member stiffness acting alone. This method of design normally does not include the beneficial effects of load sharing and composite action nor the detrimental effects of component variability. Design analysis based upon a joist-acting-alone behavior assumption does not necessarily describe the behavior of floors within the design. The effects of structural interaction and component variability need to be evaluated for floor behavior to be accurately predicted.
September, 1974.
Keywords: Floors, Wooden